The Influence of Work Competence, Work Motivation, and Work Discipline on Police Work Achievement (Case Study on the Security Intelligence and Samapta Units of the Banyumas City Police Resort) - Fadzilah, Rizqiya Nur; Purnadi, Purnadi; Darmawan, Akhmad; Randikaparsa, Irawan (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the Effect of Work Competence, Work Motivation, and Work Discipline on Police Work Achievement (Case Study on the Security Intelligence and Samapta Units of the Banyumas City Police Resort). The method used is descriptive quantitative with a research population of 129 police officers and the sampling technique used is saturated sample. Data analysis using multiple linear regression with SPSS software version 26. The results showed that Work Competence and Work Motivation had a positive and significant effect on Work Achievement. Meanwhile, Work Discipline has no significant effect on Work Achievement.